“CATUR KARANA” IDA BAGUS GEDE PURWA STUDY OF SANGGIT LAKON (KAWI CARITA) BALINESE SHADOW PUPPET - Widnyana, I Kadek; Sedana, I Nyoman; Sudarta, I Gusti Putu; Mawan, I Gede (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
Balinese Wayang kulit contains deep philosophy and aesthetics, with plays that are not only entertaining, but also contain moral teachings and life values. An important element in the structure of the play is the concept of "Catur Karana" created by Ida Bagus Gede Purwa. This research uses a qualitative method with a text analysis and phenomenology approach, involving literature study, interviews with puppeteers, audiences and practitioners of the puppet arts. Data is analyzed through text analysis and semiotics to understand the meaning and structure of the story. The research results show that "Catur Karana" is a basic method in building a new play. Dalang needs to understand the four main elements: swamandala, antakarana, uparengga, and pasiat, which support the structure of the play in Reka Sadana. Catur Karana includes five elements (panca reka) and is equipped with Catur Perakreti and Panca Wilasa materials as raw materials for creating new plays, which is an important method in nynggit plays.Qualitative research methods using text analysis and phenomenology approaches explore the application of the concept of "Catur Karana" in the Balinese Wayang kulit play by Ida Bagus Gede Purwa. The main data analyzed came from the Purwa Wasana text and the Kawi Carita text and their documentation. Data collection, literature study, interviews, and art practitioners. Narrative data analysis of text and play structure. Catur Karana by Ida Bagus Gede Purwa in the Purwa Wasana Textbook. Understand the drupadi competition play from the main play (Ramayana, Mahabharata), memorize the characters, understand the structure of the play, characterization, scenes, building blocks, pedum coral, and understand the theme. Ida Bagus Gede Purwa implemented Catur Karana into a play called the Drupadi Competition. In it, elements of chess karana are explored which are presented as a summary of the story, scenes and scenes.